The Effect of Memorable Tourism Experience on Storytelling Behavior and Revisit Intention in Jatiluwih Tourism Village - Bulan Purnama Sari; Luh Yusni Wiarti; I Wayan Mertha (Jurnal Impresi Indonesia, 2024)
Memorable Tourism Experience is one of the sources that are an aspect of excellence for a tourist destination or tourist attraction because a memorable experience will have a long- term impact. Good storytelling behavior and getting satisfaction that is in accordance with expectations will have an impact on tourist behavior to do branding and the intention to revisit. This study was conducted to see how much influence an impressive tourism experience has on storytelling behavior and revisit intention in Jatiluwih Tourism Village. The phenomenon that drives this study is the large number of storytelling behaviors of tourists who upload and convey information about their experiences through social media. The gap in previous studies is used as a novelty in this study to test how much influence memorable tourism experience has on revisit intention through storytelling behavior in Jatiluwih Tourism Village. The sampling technique used purposive sampling with a questionnaire distribution of 210 respondents consisting of domestic and foreign tourists. The type of research uses a quantitative approach using a Likert scale and data analysis using SmartPLS. The results of this study indicate that there is a significant direct influence between the memorable tourism experience variable on revisit intention, there is a significant direct influence between memorable tourism experience on storytelling behavior, there is a significant direct influence on storytelling behavior on revisit intention and storytelling behavior has a significant direct influence. In fully mediating an impressive tourism experience on the intention to revisit in Jatiluwih Tourism Village.